ISCHEMIA/REPERFUSION EFFECT ON PANCREATIC VOLUMETRICAL BLOOD FLOW VELOCITY - Dmytry Kolmykov; Sergey Alehin (Belgorod National Research University, 2015)
We investigate blood flow velocity at ischemia/reperfusion early stages. Transient hyperemia absence after ischemia/reperfusion cased by pancreatic edema development at early stages confirmed by Wet/Dry ratio elevation and morphological changes was determined.